(3GdZQa GdMeQGAs (3LQGFe MbjbjI ef SQGOjH GdQYH GdQbej Ydi GdOGQc hjHs - (3GdSjO, CMeO eMeOs ((3GdbGgQIs (3GdSMGH ddfTQ hGdJhRjYs, 2024)
(3aj bdH GdXdGe GdcGef aj SQGOjH GdEfJQfJ GdeXde jJNP GdQYH TcdkG BNQ, MjK JfZeS YGQVI GdCRjGA GdLejdI hGdSGMQI aj cGHhS dG jQhi EdG HLQCI HYO Cf COQL GSegG Vef bGFeI VMGjG eCSGhjI dehGbY GdZQa GdMeQGA , Jdc GdehGbY GdeXdeI GdJj CUHMJ eSQMkG dJLGQI GdHTQ, MjJ Je GNJWGagG hJNOjQgG hoJSde caOjI dd (B"(3GdehJ GdCShO(B" (3Jdc GdLeGYI GdSQjI GdJj JQYH Gddjd hJJSGQY fHVGJ GdbdH hJJUGYO ehLGJ GdQYH eY eVj GdhbJ, MjK jbJQH ehYO HjYgG dedjhfjQGJ SGOjjf jJdPPhf HJbWjY CLSGO GdVMGjG CMjGA bHd Cf JdJge GdfehQ GTdGFge aj dYHI MbjbjI eQhYIs
Keywords: (3GdJcfhdhLjGs -- (3GdLhGfH GdGLJeGYjIs; (3GdLQjeI hGdeLQehfs; (3GdMGSHGJ GdEdcJhQfjIs